2020
DOI: 10.15252/embj.2020106228
|View full text |Cite
|
Sign up to set email alerts
|

Viral nucleoprotein antibodies activate TRIM21 and induce T cell immunity

Abstract: Nucleoprotein (N) is an immunodominant antigen in many enveloped virus infections. While the diagnostic value of anti‐N antibodies is clear, their role in immunity is not. This is because while they are non‐neutralising, they somehow clear infection by coronavirus, influenza and LCMV in vivo. Here, we show that anti‐N immune protection is mediated by the cytosolic Fc receptor and E3 ubiquitin ligase TRIM21. Exploiting LCMV as a model system, we demonstrate that TRIM21 uses anti‐N antibodies to target N for cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 46 publications
1
64
0
Order By: Relevance
“…Certainly, the question raised here is due to the vaccine used in this study being inactivated, enabling the simultaneous presentation of S and N antigens based on its technological production strategy. However, previous studies on the antigenicity of the N protein in the coronavirus 229E strain suggested that the anti-N antibody of CoV-2 would be involved in promoting a protective CTL cell response [ 11 ], and clinical immunological detection of COVID-19 patients also identified the existence of N antibodies in sera of infectious and convalescent periods [ 12 ]. To some extent, the observation in this study that neutralizing antibodies wane after reaching their peak does not mean the vanishing of effect immunity in individuals administered two doses of inactivated vaccine is logical.…”
mentioning
confidence: 99%
“…Certainly, the question raised here is due to the vaccine used in this study being inactivated, enabling the simultaneous presentation of S and N antigens based on its technological production strategy. However, previous studies on the antigenicity of the N protein in the coronavirus 229E strain suggested that the anti-N antibody of CoV-2 would be involved in promoting a protective CTL cell response [ 11 ], and clinical immunological detection of COVID-19 patients also identified the existence of N antibodies in sera of infectious and convalescent periods [ 12 ]. To some extent, the observation in this study that neutralizing antibodies wane after reaching their peak does not mean the vanishing of effect immunity in individuals administered two doses of inactivated vaccine is logical.…”
mentioning
confidence: 99%
“…Due to the S-RBD antibody's capacity to interfere with the entrance of the virus into host cells and thus prevent replication, S-RBD is a widely used target in vaccine development (28,29). Conversely, as NP only exists inside the virus and is wrapped around the ribonucleic acid, the NP antibody is barely capable of blocking the virus's entrance, but could protect the host via the activation of T-cell immunity (30). Further, as the NP's mutation rate is relatively low, NP is another potential target for vaccine development (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although, these are likely to be non-neutralising antibodies, they often have the ability to clear viral infections [54][55][56]. Additionally, recent reports using lymphocytic choriomeningitis virus (LCMV) as a model virus suggest an alternative mechanism for the beneficial effect of N protein specific antibodies which involves the stimulation of antibody-dependent intracellular neutralisation and promotion of N specific cytotoxic T lymphocytes (CTLs) that efficiently clear virus infected cells [57]. The study by Caddy et al suggests that N-specific antibodies can bind N protein either released during viral lysis or expressed on the surface of infected cells and that the immune complex can be taken up by APCs, in which TRIM21 targets N protein for cytosolic degradation and the generation of cytotoxic T cells against N peptides.…”
Section: Discussionmentioning
confidence: 99%